Development And Implementation Of Improved Coded OFDM System Using SDR Platform - Hamid, Hamood Shehab (2010)
he increasing demand for high speed wireless connectivity at low cost poses new challenges for communication system designers, to implement solutions that increase the data rate by utilizing the limited radio resources more efficiently at a low additional complexity. Adaptive Coding and Modulation (ACM) exploits the flexibility of channel coding and constellation in Orthogonal Frequency Division Multiplexing (OFDM) to obtain higher data rates. This technique employs multiple modulation and coding schemes to instantaneously adapt to the variations in the channel Signal to Noise Ratio (SNR), thus maximizing the system throughput and improving Bit Error Rate (BER) performance. On the other hand, OFDM system suffers from inter-symbol interference (ISI), especially in mobile communication environments. This problem may be tackled by increasing the individual symbol duration for each subcarrier together with the use of guard time. Nevertheless, this does not solve the problem completely in multipath fading channel, because all subcarriers will arrive at the receiver with different amplitudes. Unfortunately, some subcarriers may be completely lost because of deep fades. Hence even though most subcarriers may be detected without errors, the overall BER will be largely dominated by a few subcarriers with bad SNR. To eliminate this problem, OFDM based systems usually employ a special technique like error correction coding (ECC). Various coding methods are adopted by many standards to mitigate the effects of frequency selective channel which causes bit errors to occur in burs